The proposed Ministry of Health - Davies, Margaret Llewelyn, 1861-1944 ; Phillips, Marion, 1881-1932 ; Webb, Emily; MacArthur, Mary R. (Mary Reid), 1880-1921
1918 1918 1910s 2 pages (2) The inclusion in the organisation of the Ministry of a strong Maternity Department largely staffed by women. (3) The exclusion of any representation of "interests" in the Ministry. (4) The power to take over Health Services now administered through other Departments. II. That legislation establishing the Ministry of Health should be accompanied by an extension of the powers of the local Public Health Authorities in regard to Maternity and Infancy work. III. That reports should be prepared immediately on such questions as: (a) The co-ordination of the various local administrative bodies. (b) Medical, Midwifery, and Nursing Services, (c) The position of women under the Insurance Act. Such reports, for which information is already largely available, would allow discussion of the difficult problems which must be settled if the Ministry is to be efficient, and should be carried on while the Bill is before the House, so that, immediately upon its formation, the new Ministry may proceed unhampered in the work before it. The above proposals make Insurance an "integral part" of the Ministry — as is rightly demanded. At the same time the broad policy that Public Health, and not Insurance, must be the basis of the work is insisted on by transferring all the public health work of the Local Government Board to the new Ministry, and by the immediate extension of the power of the Local Health Authorities as regards Maternity and Infancy work which is an urgent matter in view of rising prices and the present large industrial employment of women. The claim that Public Health should be the basis of the Ministry is paramount,— (1) Because the benefit of the general public, and not a particular class of persons, is the underlying principle of the Public Health Services, while Insurance deals with a limited class. (2) Because the Public Health Services are essentially preventive in character. (3) Because they are under the control of directly-elected persons. (4) Because the machinery for carrying out all Public Health work is already organised in clearly defined geographical areas by the local Public Health Authorities. We therefore make these proposals in the hope that the obstruction caused by the conflicting views of the Departments concerned may be overcome in the public interest. (Signed) MARY R. MACARTHUR (Women's Trade Union League and National Federation of Women Workers). MARGARET LL. DAVIES (Women's Co-operative Guild). MARION PHILLIPS (Women's Labour League). E. WEBB (Railway Women's Guild). 36/H24/3